2019
DOI: 10.18502/ijph.v48i2.831
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Two-Dimensional plus Four-Dimensional Ultrasonography in Fetal Craniocerebral Anomalies

Abstract: Background: To assess the clinical value of two-dimensional (2D) plus four-dimensional (4D) ultrasonography in diagnosis of fetal craniocerebral anomalies. Methods: Retrospective analysis was performed on the sonographic features of 83 maternity patients admitted to Northwest Women’s and Children’s Hospital, Xian China from January 2013 to December 2017 diagnosed with suspected fetal anomalies of the brain and skull through 2D and 4D ultrasonography. Results: Fifty six patients were diagnosed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Wang et al [25] used 2D and 4D to estimate the diagnostic value in fetal craniocerebral malformations. They reported that, the accuracy of 4D alone was significantly higher than 2D and combined approaches [2D plus 4D] accuracy was better than each modality alone.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [25] used 2D and 4D to estimate the diagnostic value in fetal craniocerebral malformations. They reported that, the accuracy of 4D alone was significantly higher than 2D and combined approaches [2D plus 4D] accuracy was better than each modality alone.…”
Section: Discussionmentioning
confidence: 99%